Analysis Of Determinants Of Working Hours And Income Of Women Traders (Case Study Of Culinary Traders In Jembrana Regency) - Aliffia Putri Damayanti; Ni Made Tisnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Increasing needs make the income earned by men as heads of families increasingly difficult, this situation has resulted in many women contributing to find additional income for the family. Generally, most female workers are in trade jobs, especially in the culinary sector. The increase in income of female culinary traders in this study can be influenced by several factors, namely education level, number of family dependents, marital status, migration status, and working hours. This research aims to analyze the direct and indirect influence of education level, number of family dependents, marital status, migration status, and working hours on income. The number of samples taken was based on calculation results using the Slovin formula with a population of 3,696, namely 97 people. The data analysis techniques used are descriptive analysis techniques and path analysis. The results of this research show that 1) Education level, number of family dependents have a positive and significant effect on working hours. 2) Female culinary traders who are married have a higher number of working hours than those who are not married. 3) Female culinary traders with migrant status have a higher number of working hours than non-migrants. 4) Education level, number of family dependents, working hours have a positive and significant effect on income. 5) Female culinary traders who are married earn higher incomes than those who are not married. 6) Female culinary traders with migrant status earn higher incomes compared to non-migrants. 7) The amount of working hours mediates the influence of education level, number of family dependents, marital status, and migration status on the income of female culinary traders in Jembrana Regency.